Detection of coherent optical phonons in a thin bismuth film by ultrafast electron diffraction. (March 2020) - Mironov, B.N.; Aseyev, S.A.; Ischenko, A.A.; Kochikov, I.V.; Chekalin, S.V.; Ryabov, E.A.
Abstract: Coherent dynamics of lattice oscillations in a ∼20-nm-thick film obtained by thermal sputtering of bismuth is studied using ultrashort electron bunches synchronised with femtosecond laser pulses irradiating the sample. The Fourier analysis of ultrafast electron diffraction (UED) data shows that the observed modulation of the signal is due to the ensemble of modes corresponding to optical phonons with frequencies of approximately 3, 6 and 9 THz. A conclusion is made that these peaks correspond to the manifestation of the bismuth A 1g mode (three-terahertz peak), as well as its first and second overtones, which is probably due to quantum confinement in a 20-nm Bi nanostructure. The possibility of a detailed study of the quantum-size effect in bismuth with the help of a transmission UED is analysed.